2016
DOI: 10.1016/j.ecoleng.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Within-lake variability and environmental controls of sediment denitrification and associated N2O production in a shallow eutrophic lake

Abstract: Excess nitrogen (N) in lakes may lead to eutrophication and many attendant environmental problems such as water quality decline and loss of aquatic biodiversity. Denitrification in lake sediments can alleviate the effects of eutrophication through removal of N to the atmosphere as N2O and N2. However, N2O contributes to the greenhouse effect and global warming. In this study, we measured three denitrification parameters (i.e., potential denitrification rate, unamended denitrification rate and net N2O productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In some cases, C availability is considered as one of the most important factor regulating the sediment denitrification rates . Consistent with previous work conducted in the Yangtze River basin (e.g., Yao et al, 2016), our study found that there was no significant relationship between denitrification rates and C concentrations in water or sediments (Table 3). This result can be due to the high concentration of C in sediments and suggests that sediment denitrification rates of Yangtze lakes are not limited by the availability of C.…”
Section: Sediment Denitrification Rates Of Macrophyte-rich and Macropsupporting
confidence: 92%
See 3 more Smart Citations
“…In some cases, C availability is considered as one of the most important factor regulating the sediment denitrification rates . Consistent with previous work conducted in the Yangtze River basin (e.g., Yao et al, 2016), our study found that there was no significant relationship between denitrification rates and C concentrations in water or sediments (Table 3). This result can be due to the high concentration of C in sediments and suggests that sediment denitrification rates of Yangtze lakes are not limited by the availability of C.…”
Section: Sediment Denitrification Rates Of Macrophyte-rich and Macropsupporting
confidence: 92%
“…However, this significant correlation was not detected in macrophyte‐free lakes. The positive relationship between N content and denitrification rate has been frequently observed, because NO 3 − is the terminal electron receptor of denitrification process and a high NO 3 − level in lake water can directly enhance the sediment denitrification rates (Garcı́a‐Ruiz et al, ; Liu et al, ; Yao et al, ). In macrophyte‐free lakes, background denitrification rate increased with increasing sediment moisture (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excess N is directly linked to numerous environmental issues at different scales, including climate change, N deposition, river and lake acidification, water quality deterioration, forest productivity decline, and biodiversity loss (Driscoll et al 2001;Magill et al 2004;Compton et al 2011;. Denitrification is known to be the most important N removal process, converting nitrate (NO 3 -) to nitrous oxide (N 2 O) and dinitrogen (N 2 ), which are then released into the atmosphere (Bettez and Groffman, 2012;Yao et al 2016;Xiong et al 2017). It has been estimated that global terrestrial, freshwater, and marine ecosystems can remove approximately 313 Tg N annually through the denitrification process (Seitzinger et al 2006).…”
Section: Introductionmentioning
confidence: 99%